Diversity oriented synthesis of tricyclic compounds from glycals using the ferrier and the pauson-khand reactions - Hotha, Srinivas; Tripathi, A. (Journal of Combinatorial Chemistry, 2005)
Diversity oriented synthesis of tricyclic compounds was achieved using a combination of the Ferrier reaction and the Pauson-Khand reaction. Ferrier reaction was effected using NbCl5, and the Pauson-Khand reaction was carried out using CO2(CO)(8), acetonitrile-dimethoxyethane. Michael additions using various alkyl, aryl, and heterocyclic thiols were also performed successfully. The Ferrier, Pauson-Khand, and Michael addition reactions were found to be highly diastereoselective.

Niobium(V) chloride catalyzed microwave assisted synthesis of 2,3-unsaturated O-glycosides by the Ferrier reaction - Hotha, Srinivas; Tripathi, A. (Tetrahedron Letters, 2005)
NbCk catalyzes the Ferrier reaction of per-O-acetylated glycals with primary, secondary, altylic, benzylic and monosaccharide alcohols to give 2,3-unsaturated alpha-glycosides in short reaction times under microwave irradiation conditions. (c) 2005 Elsevier Ltd. All rights reserved.